Sequencing of BRAF inhibitors and ipilimumab in patients with metastatic melanoma: a possible algorithm for clinical use - Ascierto, Paolo A; Simeone, Ester; Giannarelli, Diana; Grimaldi, Antonio M; Romano, Anna; Mozzillo, Nicola (Journal of translational medicine, 2012)
Background Ipilimumab and vemurafenib have both been shown to improve survival in phase III trials of patients with metastatic melanoma. Although vemurafenib is associated with a rapid onset of activity, responses are often of limited duration. Conversely, responses to ipilimumab take time to develop, but can be durable. Currently, limited data exist on the sequencing of these agents in patients with the BRAF V600 mutation. The aim of this analysis was to identify factors that could potentially be used to optimise the order in which ipilimumab and BRAF inhibitors are administered in this patient population. Methods This was a retrospective, single-institution, analysis of patients treated with vemurafenib 960 mg or dabrafenib 150 mg twice-daily and ipilimumab 3 mg/kg every 3 weeks for 4 doses as part of a clinical trial or expanded access program. Eligible patients tested positive for the BRAF V600 mutation and had sequentially received treatment with vemurafenib or dabrafenib followed by ipilimumab, or vice versa. Results In total, 34 BRAF-mutation positive patients were eligible, comprising six patients who received ipilimumab followed by a BRAF inhibitor, and 28 patients treated with a BRAF inhibitor who subsequently received ipilimumab. Of these 28 patients, 12 (43 %) had rapid disease progression resulting in death and were unable to complete ipilimumab treatment as per protocol. These patients were classified as having rapid disease progression. Median overall survival for rapid progressors was 5.7 months (95 % CI: 5.0–6.3), compared with 18.6 months (95 % CI: 3.2–41.3; p < 0.0001) for those patients who were able to complete ipilimumab treatment. Baseline factors associated with rapid progression were elevated lactate dehydrogenase, a performance status of 1 and the presence of brain metastases. Patients were more likely to have rapid disease progression if they had at least two of these risk factors at baseline. Conclusions Our analysis suggests it may be possible to identify those patients at high risk of rapid disease progression upon relapse with a BRAF inhibitor who might not have time to subsequently complete ipilimumab treatment. We hypothesise that these BRAF-mutation positive patients may benefit from being treated with ipilimumab first.